The impact of Biopreservatives and Storage Temperature in the Quality and Safety of Minimally Processed Mixed Vegetables for Soup - Alvarez, María Victoria (2015)
BACKGROUND: The combined effects of bioactive agents (tea tree essential oil, propolis extract and gallic acid) and storage temperature on the microbiological and sensory quality of fresh-cut mixed vegetables for soup (celery, leek and butternut squash) were studied with the objective of preserving its quality and safety. RESULTS: Refrigeration temperature was confirmed as the main factor to limit the growth of spoilage and pathogenic microorganisms. Biopreservatives applied on mixed vegetables were effective only when combined with optimal refrigeration temperature (5 °C). Bioactive compounds showed slight effectiveness in controlling the microbiota present in mixed vegetables, although coliforms were greatly reduced by gallic acid and propolis treatments, achieving 0.5-2 log unit reductions during storage. Also, these agents showed antimicrobial activity against endogenous Escherichia coli and inoculated E. coli O157:H7, exerting a bacteriostatic effect and reducing population counts by 0.9-1.2 log CFU g-1 at 10 days of refrigerated storage. The combination of propolis treatment with refrigerated storage conditions effectively preserved the sensory quality and prolonged the sensory shelf life of fresh-cut mixed vegetables by 3 days. CONCLUSION: The use of natural agents such as propolis extract to preserve the quality and safety of mixed vegetables for soup might be an interesting option to address the concerns of the consumer about the use of synthetic chemical antimicrobials potentially harmful to health.